What’s in a name? Problems, facts and controversies regarding neurological eponyms - Hélio A. G. Teive; Plínio M. G. Lima; Francisco M. B. Germiniani; Renato P. Munhoz (Arquivos de Neuro-Psiquiatria)
ABSTRACT The use of eponyms in neurology remains controversial, and important questions have been raised about their appropriateness. Different approaches have been taken, with some eponyms being excluded, others replaced, and new ones being created. An example is Hallervorden-Spatz syndrome, which has been replaced by neurodegeneration with brain iron accuulatium (NBIA). Amiothoplic lateral sclerosys (ALS), for which the eponym is Charcot’s disease, has been replaced in the USA by Lou Gehrig’s disease. Guillain-Barré syndrome (GBS) is an eponym that is still the subject of controversy, and various different names are associated with it. Finally,restless legs syndrome (RLS), which was for years known as Ekbom’s syndrome, has been rechristened as RLS/Willis-Ekbom syndrome.